2015
DOI: 10.1007/s12603-015-0541-9
|View full text |Cite
|
Sign up to set email alerts
|

Iron deprivation may enhance insulin receptor and Glut4 transcription in skeletal muscle of adult rats

Abstract: Dietary iron deprivation may improve insulin receptor and glucose transporter transcription in muscle; however, our results show that dietary iron restriction can prevent and/or promote oxidative damage in a tissue-specific manner, emphasizing the importance of maintaining optimal iron intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Although, we hypothesize that high intake of iron may lead to increased risk of iron overload and then enhance the generation of inflammation, which can cause insulin resistance and then hyperinsulinaemia; these conditions may reduce insulin-mediated suppression of hormone-sensitive lipase (enzyme responsible for mobilization of triglyceride), which can increase intracellular lipolysis, plasma levels of free fatty acids and their transport to the liver. The increment in the levels of liver free fatty acids motivates triglyceride-rich lipoprotein production [4348]. Also, our results are along with previous reports showing a relationship between red meat (the main source of iron) intake and high triglyceride levels [8, 16, 45].…”
Section: Discussionsupporting
confidence: 87%
“…Although, we hypothesize that high intake of iron may lead to increased risk of iron overload and then enhance the generation of inflammation, which can cause insulin resistance and then hyperinsulinaemia; these conditions may reduce insulin-mediated suppression of hormone-sensitive lipase (enzyme responsible for mobilization of triglyceride), which can increase intracellular lipolysis, plasma levels of free fatty acids and their transport to the liver. The increment in the levels of liver free fatty acids motivates triglyceride-rich lipoprotein production [4348]. Also, our results are along with previous reports showing a relationship between red meat (the main source of iron) intake and high triglyceride levels [8, 16, 45].…”
Section: Discussionsupporting
confidence: 87%
“…In general, ID was proven to increase the expression of muscle glucose transporters. However, skeletal muscle of iron‐deficient rats demonstrated an increased expression of the muscle‐specific GLUT‐4, while experimental data from in vitro studies on the myocytes suggested an increase in expression of ubiquitously distributed transporter GLUT‐1. Concerning the intensity of carbohydrate metabolism, Barrientos et al .…”
Section: Paragraph 3 Iron Deficiency and Metabolic Alterations In Skmentioning
confidence: 99%
“…Considering metabolic changes induced by ID in skeletal muscle, it can be concluded that low iron state increases non‐anaerobic glucose metabolism, thus improving glucose uptake and insulin sensitivity in this tissue. Indeed, ID is reported to improve insulin sensitivity in peripheral tissues of iron‐deficient animals possibly through an enhanced expression of the glucose transporters, but it also triggers less desirable metabolic adaptations, such as hyperglycaemia, hyperinsulinaemia, and hypertriglyceridaemia . This phenomenon may result from the ID‐induced deficiencies of mitochondrial ETC, which in turn lead to ineffective carbohydrate and fat oxidative metabolism combined with compensatory increased glucose demand.…”
Section: Paragraph 3 Iron Deficiency and Metabolic Alterations In Skmentioning
confidence: 99%
“…One mechanistic insight for the role of dietary iron has been previously published by Mehdad et al 2015; who showed that reduced dietary iron enhanced insulin receptor expression in skeletal muscle [ 32 ]. On the other hand, our results agree with those of Minamiyama et al [ 14 ], in which the effects of iron depletion on lipid profiles and glycosylated hemoglobin (HbA1c) levels were examined.…”
Section: Discussionmentioning
confidence: 99%